A year in the acoustic world of bowhead whales in the Bering, Chukchi and Beaufort seas. (August 2015) - Clark, Christopher W.; Berchok, Catherine L.; Blackwell, Susanna B.; Hannay, David E.; Jones, Josh; Ponirakis, Dimitri; Stafford, Kathleen M.
Highlights: Acoustic data: 6 groups, 20 recorders, 14 months, 2300 km, Bering to Beaufort seas. Bowhead acoustics: dynamics of regional-seasonal occurrence–distribution. Noise analysis: regional-seasonal mammal, ice, wind, human acoustic contributions. Value: Initial large-scale synthesis of arctic marine acoustic environment. Abstract: Bowhead whales, Balaena mysticetus, in the Bering–Chukchi–Beaufort (BCB) population, experience a variable acoustic environment among the regions they inhabit throughout the year. A total of 41, 698 h of acoustic data were recorded from 1 August 2009 through 4 October 2010 at 20 sites spread along a 2300 km transect from the Bering Sea to the southeast Beaufort Sea. These data represent the combined output from six research teams using four recorder types. Recorders sampled areas in which bowheads occur and in which there are natural and anthropogenic sources producing varying amounts of underwater noise. We describe and quantify the occurrence of bowheads throughout their range in the Bering, Chukchi, and Beaufort seas over a 14-month period by aggregating our acoustic detections of bowhead whale sounds. We also describe the spatial–temporal variability in the bowhead acoustic environment using sound level measurements within a frequency band in which their sounds occur, by dividing a year into three, 4-month seasons (Summer–Fall 2009, August–November 2009: Winter 2009–2010, December 2009–March 2010: and Spring–Summer 2010, April–July 2010) and their home range into five zones. Statistical analyses revealed no significant relationship between acoustic occurrence, distance offshore, and water depth during Summer–Fall 2009, but there was a significant relationship during Spring–Summer 2010. A continuous period with elevated broadband sound levels lasting ca. 38 days occurred in the Bering Sea during the Winter 2009–2010 season as a result of singing bowheads, while a second period of elevated levels lasting at least 30 days occurred during the early spring–summer season as a result of singing bearded seals. The lowest noise levels occurred in the Chukchi Sea from the latter part of November into May. In late summer 2009 very faint sounds from a seismic airgun survey approximately 700 km away in the eastern Beaufort Sea were detected on Chukchi recorders. Throughout the year, but most obviously during the November into May period, clusters of intermittent, nearly synchronized, high-level events were evident on multiple recorders hundreds of miles apart. In some cases, these clusters occurred over 2–5 day periods and appear to be associated with high wind conditions.